1992
DOI: 10.1021/bi00123a019
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of DNA-protein interactions associated with intrinsic, sequence-dependent DNA curvature

Abstract: Inherently curved DNA segments, associated with short runs of adenines, have been identified in many gene regulatory regions, yet their physiological significance remains unknown. The observations reported in this study indicate that intrinsically bent nucleic acid fragments are characterized by substantially attenuated affinities toward DNA-binding proteins involved in structural functions, such as H1 histone and protamine, as well as toward various DNA-modifying enzymes including ligases and exo- and endonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This result is consistent with the greater rate of exonucleolysis seen for (A+T)-rich sequences compared with (G+C)-rich sequences (22). In addition to increasing the melting capacity ofthe primer terminus, homopolymeric A/T runs promote primer-template slippage under certain conditions and may have an altered DNA conformation at the primer terminus that inhibits DNA binding at the polymerase site (23,24).…”
Section: Discussionsupporting
confidence: 61%
“…This result is consistent with the greater rate of exonucleolysis seen for (A+T)-rich sequences compared with (G+C)-rich sequences (22). In addition to increasing the melting capacity ofthe primer terminus, homopolymeric A/T runs promote primer-template slippage under certain conditions and may have an altered DNA conformation at the primer terminus that inhibits DNA binding at the polymerase site (23,24).…”
Section: Discussionsupporting
confidence: 61%
“…These effects were explained by assuming that the enzyme prefers a DNA substrate with a minor groove of average width. Shatzky-Schwartz et al (13) have shown that the activities of several DNA-processing enzymes, including DNase I and the exonucleases BAL31 and exoIII, are markedly impaired by the presence of repeated A-tract sequences (5′-A 4 T 4 -3′) within their duplex DNA substrates. These effects were attributed to a reduced binding affinity of the enzymes for bent regions of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of DNA structure during the past decade have shown that significant sequence-dependent deviations from the canonical B-form helical structure can occur. These differences, although small relative to differences between the "A", "B," and "Z" DNA structures, can have a pronounced effect upon sequence-independent enzymes that use duplex DNA as a substrate (13,14). Sequence-directed DNA curvature is correlated with a variety of protein-DNA interactions in vivo, and DNA bending may be important in sequence recognition by DNA-binding proteins (15).…”
mentioning
confidence: 99%
“…In addition, it was recently reported that DNA-protein interactions can be attenuated by the presence of intrinsic sequence-dependent DNA curvature (Shatzky-Schwarz et al, 1992). It is interesting to speculate whether a (+)-CC-1065-entrapped or -induced bent conformation of DNA might mimic an intrinsic or proteininduced curved DNA found in the regulatory regions of a genome, such as the promoter regions, or in replication origins (Le,, serve as a surrogate protein).…”
Section: Discussionmentioning
confidence: 99%